NMR-based metabolomics and UHPLC-ESI-MS/MS profiling of Syzygium jambos in relation to their antioxidant and anti-hyperglucemic activities - Abas, Faridah; Ramli, Nurul Shazini; Tan, Chin Ping; Azlan, Azrina; Wong, Pei Lou (Elsevier BV, 2024)
Search for natural sources in disease management especially diabetes has surged recently for its potential health benefits. However, several fruit tree species remained unpopular despite their folkloric usage due to insufficient scientific data. Syzygium jambos (L.) Alston (Myrtaceae) is a fruit-bearing plant that is used as a traditional dietary supplement to treat various diseases including diabetes. This study investigated the correlation between S. jambos leaves’ metabolites and the bioactivities using proton-nuclear magnetic resonance (1H NMR)-based metabolomics approach. In-vitro total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH•) radicals scavenging, nitric oxide (NO•) radicals scavenging, anti-α-amylase and anti-α-glucosidase assays were performed. The findings indicated that 70 % ethanolic extract demonstrated the highest potential in overall bioactivities. A total of 59 and 30 metabolites were tentatively identified using ultrahigh-performance liquid chromatography electrospray ionization Quadrupole-Orbitrap tandem mass spectrometry (UHPLC/ESI Q-Orbitrap MS/MS) and NMR, respectively. The partial least square (PLS) model revealed tannins, triterpenoids, and flavonoids significantly contributed to the separation and bioactivities. This study provides comprehensive insights into S. jambos metabolome and reveals the potential as a reliable source of antioxidant and anti-hyperglycemic compounds.